A fish and tetrapod fauna from Romer's Gap preserved in Scottish Tournaisian floodplain deposits. (3rd October 2018) - Otoo, Benjamin K. A.; Clack, Jennifer A.; Smithson, Timothy R.; Bennett, Carys E.; Kearsey, Timothy I.; Coates, Michael I.
Abstract: The end‐Devonian mass extinction has been framed as a turning point in vertebrate evolution, enabling the radiation of tetrapods, chondrichthyans and actinopterygians. Until very recently 'Romer's Gap' rendered the Early Carboniferous a black box standing between the Devonian and the later Carboniferous, but now new Tournaisian localities are filling this interval. Recent work has recovered unexpected tetrapod and lungfish diversity. However, the composition of Tournaisian faunas remains poorly understood. Here we report on a Tournaisian vertebrate fauna from a well‐characterized, narrow stratigraphic interval from the Ballagan Formation exposed at Burnmouth, Scotland. Microfossils suggest brackish conditions and the sedimentology indicates a low‐energy debris flow on a vegetated floodplain. A range of vertebrate bone sizes are preserved. Rhizodonts are represented by the most material, which can be assigned to two taxa. Lungfish are represented by several species, almost all of which are currently endemic to the Ballagan Formation. There are two named tetrapods, Aytonerpeton and Diploradus, with at least two others also represented. Gyracanths, holocephalans, and actinopterygian fishes are represented by rarer fossils. This material compares well with vertebrate fossils from other Ballagan deposits. Faunal similarity analysis using an updated dataset of Devonian–Carboniferous (Givetian–Serpukhovian) sites corroborates a persistent Devonian/Carboniferous split. Separation of the data into marine and non‐marine partitions indicates more Devonian–Carboniferous faunal continuity in non‐marine settings compared to marine settings. These results agree with the latest fossil discoveries and suggest that the Devonian–Carboniferous transition proceeded differently in different environments and among different taxonomic groups.